Analysis and Experimental Study on Pressure Characteristics of Supporting Roller Group of Pipe Belt Conveyor - Shuang Wang; Deyong Li; Kun Hu (Shock and Vibration)
Aiming at the problem in measuring the nonuniformly distributed pressure generated by the pipe belt conveyor when conveying raw coals, a hexagonal adjustable pressure measuring device for the idler group is proposed. The dynamic model of the pipe belt conveyor clamping-type roller group is established. In order to simplify the calculation process of mechanical analysis, the modal analysis is carried out to determine the factors which will influence the pressure. The pipe diameter and filling rate are selected as the key control factors by the sensitive analysis of pressure of the pipe belt conveyor clamping type roller group. An adjustable diameter-type supporting roller group experiment device is self-designed, and the dynamic pressure change of the roller group and each roller pressure are tested. The results show that the average error between the simulated and tested values of the pressure of the idler group at different filling rates is 7.3%; the theoretical and simulated values of the pressure of the idler group are in good agreement with the experimental values. The study provides a theoretical basis and experimental reference for the design and application of pipe belt conveyors.